The Bantu and the study of history (Historia, 2021)
It is a well-known fact that the teaching of history in South Africa has for at least a decade called forth a torrent of ideas and writings from the ranks of professional historians, educationists, leaders of culture, politi- cians and journalists} The airing of views is still going on. Attention was mainly focussed on the state of history in European schools and universities, but very litle, if any, thought was giv~n to the problem as far as the non-European schools or universities were concerned. If a European had dealt with the matter it was only in passing, and the non-European has on the whole preserved a stoical silence on the question of history teaching and to a large measure also in the field of historical writing. To the European South African and especially to the Afrikaner such a state of affairs is puzzling indeed, because it could have been expected that the Bantu would employ history as a component part of their political struggle -as the Afrikaner did when a mood of reaction prevailed.
Keywords: Teaching of history; South Africa; History; Bantu; African history